Straitening The Audit Expectation Gap In Zimbabwe’s Public Sector: Doing Things Right Versus Doing The Right Things (Journal of Namibian Studies : History Politics Culture, 2023)
The rapid metamorphoses in Zimbabwe’s public sector have intensified the concerns of the widening audit expectation gap between the public and the country’s supreme audit institution (SAI). Zimbabwe has been battling systemic corruption, pervasive fraudulent activities and weak finance management in the public sector.  As a consequence, three critical issues have morphed up; the litigation risks created by the auditor expectation gap, loss of trust and erosion of public confidence in the country’ SAI. The main aim of this study was to explore strategies that can be used to diminish the audit expectation gap in Zimbabwe and re-establish public buoyancy, conviction and public value of external audits. Qualitative data was collected using a combination of one brainstorming session and a focus group discussion made up of civil society organisations, accountants, audit professionals, academics and members of the public. Our findings demonstrate the need for policy makers to extend the remit of the country’s SAI to go beyond forming opinions of truthfulness and fairness of fair statements, but also to assume responsibility for detecting public corruption and fraud in the public sector. The study recommends that external auditors should produce reports that engender public trust, public sector accountability, public value and sustainable use of public resources. Hence, there is an imperative need to amend various laws that govern the SAI to bring them in tandem with international best audit standards.